problemset1s - MAT 137Y 2008-09 Winter Session, Solutions...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: MAT 137Y 2008-09 Winter Session, Solutions to Problem Set 1 1 (i) (SHE 1.3 #58) We need to show that a ab , ab a + b 2 , and a + b 2 b . Since 0 a b , we have a 2 ab , or a ab , proving the first statement. Also, a b = a + b 2 b = a + b 2 b , proving the third statement. Finally, note that ( a- b ) 2 = a 2- 2 ab + b 2 = a 2 + 2 ab + b 2 4 ab = ( a + b ) 2 4 ab = a + b 2 ab = a + b 2 ab , which proves the second statement. Therefore a ab a + b 2 b . (ii) (SHE 1.4 #62) The three midpoints of the triangle are ( c 2 , ) , ( a + c 2 , b 2 ) , and ( a 2 , b 2 ) . The equations of the three lines are thus y = 2 b 2 a- c x- c 2 , y = b a + c x , y = b a- 2 c ( x- c ) . Equating the last two equations, we get y = b a + c x = b a- 2 c ( x- c ) = b a + c- b a- 2 c x = bc 2 c- a = x = bc 2 c- a 1 b a + c- b a- 2 c = x = bc 2 c- a ( a + c )( a- 2 c ) ab- 2 bc- ab- bc = a + c...
View Full Document

Page1 / 3

problemset1s - MAT 137Y 2008-09 Winter Session, Solutions...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online